(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Ephemeral channels are ever changing like chameleons and constantly challenges the field researchers. Sampling of bed load and suspended load in a quick response mountainous channel is a test of coordination, skills and luck. The channel shows great variation in sediment size distribution of bed load sediment transport over space and time. The measurement in the field indicates that the variation in sediment size in bed load not only depends upon the favorable slope and thereby flow velocity, but also the sediment fed from the upstream. The single large sediment can affect the whole distribution in a gravel bed stream. The flash floods after the precipitation causes large particles to move due to sudden flow thrust. This could dislodge other large and small sediments in bed during its movement. The movement of large sediment causes variation in sampling as it comes closer to entrance of a bed load sampler. The bed load sampling carried out collected using modified Helley Smith Sampler in a mountain ephemeral river of Gujarat revealed large variation in the sediment size. Sudden spikes in the median diameter of the sediment sample leads to large error in prediction of bed load transport rate using various bed load equations given by different researchers. This significantly and adversely affect the chances of finding an appropriate bed load equation suitable for the study river and often compels field engineers to rely on thumb rules of estimating sediment transport rate, which may sometimes lead to undesirable surprises. This study aims to give an idea about the extent to which this variation in the sediment size is generally observed.